STUDI TENTANG SULAMAN TANGAN DI NAGARI MUNGKA KECAMATAN MUNGKA KABUPATEN LIMA PULUH KOTA - WIDIASARI, YOSI; Adriani, Adriani; Idrus, Yenni (Journal of Home Economics and Tourism, 2014)
Hand embroidery in Nagari Mungka is inherited from parent to theirdaughters. However, the citizen of Lima Puluh Kota district andsurroundings are not familiar with this. The purpose of this study is todescribe about the types of embroidery, the forms of embroidery design, thetechniques of embroider, and the type of embroidery products. This studyuses qualitative method. The type of data is primary and secondary data.The technique of collecting data through observation, interview anddocumentation. The data analysis technique which uses interactive modelanalysis that is related with subject matter is data reduction model, datapresentation, and conclusion. The results of the study are: first, the handembroidery in Nagari Mungka has six types, there are shadow embroidery,needlepoint arise embroidery, flat embroidery, fantasy embroidery, ribbonembroidery, and attach mute and sequins. Second, the design of this isnatural (plants and animals) and geometric (other objects). There havethirteen of it. There are stalk, leaf, roses, jasmine, hibiscus, sunflower, lotus,taro, tulips, butterflies, Itiak pulang patang, triangle and roda-roda isi.Third, the techniques of embroider in Nagari Mungka has two types. First,tarranging thread decoratively technique. Second, lekapan technique.Finally, the embroidery in Nagari Mungka produces material of bajukurung, materials of dress, mukenah, and veil .